2010
DOI: 10.1128/ec.00269-09
|View full text |Cite
|
Sign up to set email alerts
|

Septins AspA and AspC Are Important for Normal Development and Limit the Emergence of New Growth Foci in the Multicellular Fungus Aspergillus nidulans

Abstract: Septins are cytoskeletal proteins found in fungi, animals, and microsporidia, where they form multiseptin complexes that act as scaffolds recruiting and organizing other proteins to ensure normal cell division and development. Here we characterize the septins AspA and AspC in the multicellular, filamentous fungus Aspergillus nidulans. Mutants with deletions of aspA, aspC, or both aspA and aspC show early and increased germ tube and branch emergence, abnormal septation, and disorganized conidiophores. Strains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 44 publications
6
91
1
Order By: Relevance
“…However, since yeast septin mutants do not display the simultaneous emergence of multiple buds, AspB also appears to have a role in restricting new growth foci not seen in S. cerevisiae. A. nidulans ⌬aspA and ⌬aspC strains also show the emergence of extra germ tubes and branches, as does a septin deletion mutant in another filamentous fungus, U. maydis (1,38). Thus, the restriction of new growth foci might be a common function for septins in other filamentous fungi.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, since yeast septin mutants do not display the simultaneous emergence of multiple buds, AspB also appears to have a role in restricting new growth foci not seen in S. cerevisiae. A. nidulans ⌬aspA and ⌬aspC strains also show the emergence of extra germ tubes and branches, as does a septin deletion mutant in another filamentous fungus, U. maydis (1,38). Thus, the restriction of new growth foci might be a common function for septins in other filamentous fungi.…”
Section: Discussionmentioning
confidence: 93%
“…We recently showed that in A. nidulans septins AspA and AspC interact as AspA-GFP forms small, abnormal structures in ⌬aspC strains, while AspC-GFP does not localize in ⌬aspA strains (38). To determine whether AspB interacts with other septins, we crossed the aspB-gfp strain to ⌬aspA, ⌬aspC, ⌬aspA ⌬aspC, ⌬aspD, and ⌬aspE strains and selected progeny carrying aspB-gfp and the appropriate septin deletion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectors likely to be immediately downstream of RasA signaling are the conserved GTPase proteins ModA (Aspergillus Cdc42 homolog) and RacA, for activation of mitogen-activated protein kinase or p21-activated kinase pathways (18,24,47). Other interesting candidates that may physically or genetically interact with RasA at the plasma membrane or endomembranes are the septins and Rho proteins, both of which play roles in germination and branch formation of A. nidulans (16,26,48). Future work in this area will focus on the identification of RasA effectors to construct improved molecular models of fungal growth and morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae, septins form scaffolds that are essential for normal polarized growth, septation, and cytokinesis (Oh and Bi 2011). In filamentous fungi, septins are needed for normal septum formation and appear to delimit growth sites (DeMay et al 2009;Lindsey et al 2010;Ryder et al 2013). For example, the absence of septins in A. nidulans leads to the simultaneous emergence of multiple germ tubes and hyperbranching.…”
Section: The Cytoskeletonmentioning
confidence: 99%